Manajemen Pengelolaan Pembelajaran Tematik Metode Tahfiz Al-Qur’an Studi di MAN Cendekia Jambi (Jurnal Manajemen Kreatif dan Inovasi, 2025)
Thematic learning management in tahfiz Qur'an is a holistic and structured approach in integrating the teaching and memorization of the Qur'an with relevant Islamic themes. This approach aims to enable students not only to memorize the text of the Qur'an but also to understand and apply Islamic teachings in the context of their daily lives. Here are some important aspects in the management of thematic learning management of tahfiz Qur'an: planning: careful planning is the main key, organizing: involving the arrangement of teaching staff, classroom management and facilities, implementation: teaching and learning processes, evaluation: measuring student achievement, coaching: teachers provide support and coaching to students, collaboration: collaboration between teachers, students and parents is very important and continuous development: this includes curriculum development, teacher training and program adjustments according to the needs and development of students. With good management, the thematic learning program of tahfiz Qur'an can provide greater benefits to students, help them become more spiritually meaningful individuals, and understand Islamic teachings more deeply.